Feeding skill performance in premature infants during the first year - Pridham, Karen; Steward, Deborah; Thoyre, Suzanne; Brown, Roger; Brown, Lisa (Early human development, 2007)
Little is known about premature infants' feeding skill development and the contribution to it of biologic and environmental conditions. Explore the level and variation in feeding skill performance through the first post-term year and examine the contribution to performance of infant neonatal condition and rate of weight gain per day, maternal feeding behavior, and its interaction with neonatal condition. Study design and subjects: In this longitudinal, descriptive study, data sources included observed and videotaped in-home feeding for 45 infants < 1250 g birth weight and their mothers (age ≥ 17 years). Feeding skill performance ( fdgskill): total number of expected skills at 1, 4, 8, and 12 months, post-term age (PTA). Feeding skill performance varied widely among infants at all four assessments. At 8 and 12 months, fdgskill indicated, for a minority of infants, delay and lack of opportunity to engage in skills associated with new foods and new feeding modalities. Neonatal medical condition contributed significantly to fdgskill at 1 and 4 months, but in the predicted (negative) direction only at four months. Rate of weight gain per day contributed significantly to fdgskill at 1 and 8 months, but in the predicted direction (positive) only at one month. Maternal feeding behavior did not contribute to fdgskill, nor did it interact with infant neonatal conditions to affect fdgskill. Although infant neonatal medical status and rate of weight gain per day, before or within the span of time between assessments, accounted for some variance in feeding skill performance within the first three assessments (1, 4, and 8 months), much remains to be explained, including neuro- and oral–motor capacities to manage new foods and feeding modalities and opportunities to practice feeding skills during the last half of the first year.